Ethical Threats and Existential Safety - Liudmila, Baeva (Social Inquiry: Journal of Social Science Research, 2020)
Amidst the development of various manifestations of modern electronic culture, security, communication, and ethics issues are acquiring new features and actualization. An objective of the research is a theoretical analysis of the issues of information ethics in the information and communication environment and threats to existential security. The features of the development of information ethics in electronic culture, associated with a high level of liberalism, utilitarianism, as well as antinomy in solving the problem of freedom and security in the digital environment are revealed. Some ethical issues of virtual communication in the “human-human” and “human-AI” systems are disclosed, the main risks in this area are systematized.